Perancangan Hotel Resort bintang 5 di Pantai Sawarna Kabupaten Lebak, Banten - Dimas Sabar Nugroho; Harfa Iskandaria (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Hotel Resort is one of the accommodations for tourism destinations, Hotels Resort must have adequate views and facilities. The design of this Resort Hotel is located in Lebak Regency, Banten which has many tourist destinations such as Sawarna Beach. In the Sawarna Beach area, it is necessary to build 5 Star Hotel Resort because the quantity of hotels in the area is still very lacking to make it easier for visitors to come and will stay overnight. So the quantity of hotels or inns is not proportional to the number of visitors. The design concept at the Hotel Resort Design applies the concept of Tropical Architecture. The design concept is applied because the location is in the tropics area or the seashore and is used as a tourism place.